Penerapan Strategi Card Sort Terhadap Hasil Belajar IPA - Inekke Oktavianti; Yuni Krisnawati; R Angga Bagus Kusnanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether the application of the card sort strategy can complete the science learning outcomes of grade V students of SD Negeri 22 Lubuklinggau. The research method used is quasi-experimental. Data collection techniques in research using essay tests. Data analysis techniques with steps: determining the mean and standard deviation, normality test and one-sample test type t test calculated using SPSS 24 calculation. The results of the analysis using the one-sample test t test at a significant level ∝ = 0.05 and dk = 24 showed a p-value value of < 0.05 (0.003 < 0.05) so that it can be concluded that Hₒ was rejected and Hₐ was accepted, meaning that the average science learning outcomes of grade V students of SD Negeri 22 Lubuklinggau after the application of the significant card sort strategy were completed with categories more or equal to 75 (μₒ≥ 75). So it can be concluded that the results of science learning for grade V students of SD Negeri 22 Lubuklinggau after the implementation of the card sort strategy are significantly complete. Keyword: Applicability, Card Sort, Learning Outcomes, Socil Education.